Electronic Module for Learning Indonesian Language Based on Environmental Character Values for Grade V Elementary School - Rahmat, Hendi; Badawi, Jami Ahmad; Othman, Shamsudin Bin (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
This study aims to produce and determine the attractiveness of the Indonesian language electronic module based on environmental care character values for fifth grade elementary school students that was developed. The research method uses Research and Development (R&D), referring to the steps developed by Branch with the ADDIE design, namely analysis, design, development, implementation, and evaluation. Data collection using interviews, questionnaires, e-module product assessment sheets, teacher observation sheets, and student observation sheets. Data analysis using quantitative descriptive analysis techniques. The instrument used is an assessment scale for the attractiveness of the module, namely using a Likert scale and arranged in the form of a checklist. The results of the study showed that based on the validation of media experts obtained 82.35%, validation of material experts obtained 82.96%, validation of education practitioners obtained 80.44% so that it was categorized as very feasible. While the results of field tests on students showed that this module has a very high level of attractiveness with a percentage of 88.87%. From the results of expert validation and product trials, it can be concluded that the Indonesian language electronic module based on environmental care character values non-fiction text material is very feasible and interesting to use as teaching materials.